Sympathetic denervation-induced MSC mobilization in distraction osteogenesis associates with inhibition of MSC migration and osteogenesis by norepinephrine/adrb3. - Zhaojie Du (Public Library of Science (PLoS), 2014)
The sympathetic nervous system regulates bone formation and resorption under physiological conditions. However, it is still unclear how the sympathetic nerves affect stem cell migration and differentiation in bone regeneration. Distraction osteogenesis is an ideal model of bone regeneration due to its special nature as a self-engineering tissue. In this study, a rat model of mandibular distraction osteogenesis with transection of cervical sympathetic trunk was used to demonstrate that sympathetic denervation can deplete norepinephrine (NE) in distraction-induced bone callus, down-regulate β3-adrenergic receptor (adrb3) in bone marrow mesenchymal stem cells (MSCs), and promote MSC migration from perivascular regions to bone-forming units. An in vitro Transwell assay was here used to demonstrate that NE can inhibit stroma-derived factor-1 (SDF-1)-induced MSC migration and expression of the migration-related gene matrix metalloproteinase-2 (MMP-2) and downregulate that of the anti-migration gene tissue inhibitor of metalloproteinase-3 (TIMP-3). Knockdown of adrb3 using siRNA abolishes inhibition of MSC migration. An in vitro osteogenic assay was used to show that NE can inhibit the formation of MSC bone nodules and expression of the osteogenic marker genes alkaline phosphatase (ALP), osteocalcin (OCN), and runt-related transcription factor-2 (RUNX2), but knockdown of adrb3 by siRNA can abolish such inhibition of the osteogenic differentiation of MSCs. It is here concluded that sympathetic denervation-induced MSC mobilization in rat mandibular distraction osteogenesis is associated with inhibition of MSC migration and osteogenic differentiation by NE/adrb3 in vitro. These findings may facilitate understanding of the relationship of MSC mobilization and sympathetic nervous system across a wide spectrum of tissue regeneration processes.